PARTICIPATORY EVALUATION AS EDUCATIONAL OUTREACH: WORKING IN UNSETTLING TIMES - Harris, Carol (Canadian Journal of Education/Revue canadienne de l'éducation, 2007)
In the context of information and communication technologies in five Newfoundland coastal communities, this article deals with participatory research and outreach. Outreach in these communities, reeling from the near‐collapse of the fishery and struggling to survive in a climate of neo‐liberal restructuring, is considered to be a holistic educational enterprise involving new technologies and the popular media, schools, and their district officers, clinics and regional health care providers, and children and adults as lifelong learners. Based on five approaches that emerged in the final year of one project ‐‐ the work of an on‐site liaison, a residential workshop, community workshops, reports through popular media, and contacts with outside organizations – the author argues that outreach should be recognized as integral to all stages of participatory research. Key words: educational outreach, participatory research, ICT, coastal communities Tenant compte des technologies de l’information et des communications dans cinq localités côtières de Terre‐Neuve, cet article porte sur les recherches concertées et l’action communautaire. La prestation de services à ces communautés, durement touchées par la quasi‐disparition de la pêche et luttant pour survivre dans un climat de restructuration néolibéraliste, est considérée comme une entreprise pédagogique holistique faisant appel aux nouvelles technologies et aux médias grand public, aux écoles et aux membres des commissions scolaires, aux cliniques et aux fournisseurs de soins de santé régionaux ainsi qu’aux enfants et aux adultes apprenant à tout âge. À la lumière des cinq approches qui ont émergé lors de la dernière année de l’un des projets, à savoir le travail d’un agent de liaison sur place, un atelier résidentiel, des ateliers communautaires, des comptes rendus par le biais de médias grand public et des contacts avec d’autres organisations, l’auteure soutient que l’action communautaire devrait être reconnue comme un élément faisant partie intégrante de tous les stades d’une recherche concertée. Mots clés : action communautaire dans le domaine de l’éducation, recherche concertée, TIC, localités côtières.